Fungos micorrízicos arbusculares e fungos endofíticos melanizados septados em gradiente de estresse abiótico no semiárido nordestino - Cruz, Iury Leite da (2024)
The research is inserted in the Brazilian semi-arid region, covering the phytogeographical domains of the caatinga, dry forests, cerrado, and humid-subhumid mountain forest. Arbuscular mycorrhizal fungi (AMF) carry out mutualistic associations with roots, the fungi use carbohydrates from the host plant and the host plant benefits from mineral nutrition. The hyphae inside the root, vesicles and arbuscules, penetrate the cell walls of the cortex cells. Dark Septate are melanized endophytic fungi, which, similar to mycorrhizae, perform symbiosis with the roots of host plants. They are common in different ecosystems and provide plants with a series of benefits, in addition to promoting soil structure. Plants harbor both AMF and DSE. Al-though a recent study, it has already been observed that dark mycelium endophytes are as abundant as AMF and can also promote plant growth in extreme environments. The objective of this work was to verify the occurrence of AMF and DSE by evaluating the number of AMF spores and root colonization by AMF and DSE in three conservation units in the Brazilian semi-arid region: Ubajara National Park, Sete Cidades National Park and Estação Ecology of Aiuaba, in addition to verifying the influence of soil attributes, aridity index and altitude on the occurrence of these fungi. All roots studied showed colonization by AMF and DSE. The effect of the Stress Gradient Hypothesis on root colonization is observed, especially in Aiua-ba. Sampling took place in the dry months. The results corroborated most studies on mycor-rhizae and Dark Septate.